USING GOOGLE FORMS TO TEST KNOWLEDGE IN GENERAL AND INORGANIC CHEMISTRY - Krupko, Olena; Holovata, Khrystyna; Udod, Sofiia (SWorld-Ger Conference proceedings, 2025)
Monitoring the level of knowledge of students is one of the important components of the educational process, which makes it possible to assess the success of learning. Analysis of the results of monitoring the level of knowledge makes it possible to adjus